Utilización de la limitación de contactos en el entrenamiento en fútbol: afecta a las demandas físicas y fisiológicas? - Casamichana, D.; San Roman-Quintana, J.; Calleja-Gonzalez, J.; Castellano, J. (Revista Internacional de Ciencias del Deporte, 2013)
The aim of this investigation was to examine the influence of the number of contacts allowed by individual possession in the physical and physiological demands during situations of small-sided games (SSG) 6 vs. 6 + 2 floaters where the aim was to support the ball possession, there being altered only the number of authorized contacts by possession (1 contact, 2 contacts and free contacts). Fourteen semiprofessional soccer players (age: 23.1 ± 4.5 years; height: 176.9 ± 3.3 cm; I weight: 73.4 ± 5.2 kg) were monitored by GPS devices (10 Hz) and bands of heart rate. The following variables were registered: heart rate average and maximum heart rate, distance, covered distance at different ranges of speed, player load, maximum speed, ratio work: rest and number of accelerations. The results showed that variable number of contacts concerns the physiological and physical demands. Specifically, major heart rate responses were observed during the SSG realized to two contacts maximum with regard to free contacts, whereas a major number of low intensity accelerations were estimated for the format of two contacts in comparison to the free contact. Significant differences were not observed for the rest of studied variables. These results provide information to the coaches to understand how the modification of different variables in the SSG concerns the physical and physiological demands of the players and, therefore, to attend to them to modulate his intensity depending on the aims of training.